Ecological citizenship in the textbook of Pancasila and Civic Education subjects at secondary level school - Rianda Usmi; Mukhamad Murdiono (Universitas Negeri Yogyakarta, 2021)
This study was conducted to (1) identify the content of ecological citizenship in the Pancasila and Citizenship Education subject textbook and (2) describe the development of ecological citizenship as teaching material in Pancasila and Citizenship Education subjects at the secondary education level. This study used a descriptive qualitative approach with content analysis methods. Data collection was carried out through reading, observing the contents of the book, and taking notes with careful analysis of the ecological citizenship content contained in the textbook. The unit of analysis in this study was the content of ecological citizenship in the form of text, material descriptions, pictures, tables, and student competency test assignments containing material about the environment. The data were analyzed by examining the content on each page of the book, which consisted of several stages which are (1) data collection; (2) recording; (3) reduction; (4) conclusions; (5) description of study results. The results showed that thematically there was no material content that focused and specifically discussed ecological citizenship in the Pancasila and Citizenship Education subject textbook at secondary education. Limited content of the new environment was presented via pictures and short descriptions. The development of ecological citizenship in the Pancasila and Citizenship Education subject was carried out by developing core competencies and basic competencies of Pancasila and Citizenship Education which emphasize the formation of knowledge, skills, character of ecological citizenship competencies